Avaliação da existência de correlação entre o espaço aéreo supero-anterior e processos patológicos de conchas nasais inferiores de pacientes submetidos à cirurgia ortognática - Silva, Onassis Leme da (2017)
Dentofacial anomalies cause aesthetic, social and mainly functional damages to the patient. The supero-anterior air space is a factor that exhibits great importance in the planning of orthognathic surgery, since the facial pattern can influence changes and modifications in its morphology and functioning. Respiratory adaptation guided by facial and occlusal dysfunctions can trigger several types of dysfunctions. In this sense, to allow certain movements or when they are hypertrophic and causing chronic respiratory obstruction, the surgical removal of the inferior nasal conchae is indicated in the surgical act. However, there is no consensus as to whether there is a relationship between upper and lower air space with the pathological pattern of the lower nasal conchae in patients with dentofacial anomalies submitted to orthognathic surgery. Therefore, the objective of this study was to verify if there is a correlation between upper-anterior air space and the pathological process of inferior nasal conchae of patients submitted to orthognathic surgery. Computed tomography of the conical bundle and lower nasal conchae were obtained from the collection of the pathology laboratory of the University of Sacred Heart removed from patients submitted to orthognathic surgery and submitted to staining and counting of the inflammatory cells. The upper-anterior airspace was measured using the Dolphin Imaging 11.9 software. Afterwards, the data were interpreted and submitted to Pearson's linear correlation test using a significance level of 5%. There was no significant correlation between air space and inflammatory tissue variables, only the macrophage obtained a moderate correlation. Therefore, we conclude that there is no significant correlation between the volume of air space and the inflammatory process of the lower nasal conchae of patients who underwent orthognathic surgery.